2007
DOI: 10.1111/j.1399-3054.2007.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Leaf senescence and N uptake parameters as selection traits for nitrogen efficiency of oilseed rape cultivars

Abstract: The cultivation of N‐efficient oilseed rape cultivars could contribute to a reduction of the large N balance surpluses of this crop. To facilitate the breeding process of N‐efficient cultivars, the identification of secondary plant traits correlating with N efficiency is necessary. The objectives of this study were to investigate leaf senescence and N uptake parameters of oilseed rape cultivars and doubled haploid (DH) lines with contrasting N efficiency in a short‐term nutrient solution experiment and to rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(33 citation statements)
references
References 41 publications
2
30
0
1
Order By: Relevance
“…Large research projects investigating and generating genetic diversity for NUE in rapeseed have been recently completed or are currently in progress, in France ( R A P S O D Y N : w w w. r a p s o d y n . f r ) , i n G e r m a n y (PreBreedYield: Samans et al 2013), and in the UK (NUECrops: http://research.ncl.ac.uk/nefg/nuecrops/). Good et al (2007) demonstrated the promise of alternative breeding technologies in generating new diversity by improving the NUE of rapeseed through the overexpression of a barley alanine aminotransferase gene in the roots.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Large research projects investigating and generating genetic diversity for NUE in rapeseed have been recently completed or are currently in progress, in France ( R A P S O D Y N : w w w. r a p s o d y n . f r ) , i n G e r m a n y (PreBreedYield: Samans et al 2013), and in the UK (NUECrops: http://research.ncl.ac.uk/nefg/nuecrops/). Good et al (2007) demonstrated the promise of alternative breeding technologies in generating new diversity by improving the NUE of rapeseed through the overexpression of a barley alanine aminotransferase gene in the roots.…”
Section: Resultsmentioning
confidence: 99%
“…Genetic variation in the activity of various nitrate and ammonium transporters, which move N across membranes, could be relevant for nitrogen uptake efficiency in rapeseed (Schulte auf 'm Erley et al 2007) and should be further studied (reviewed in Xu et al 2012).…”
Section: Nitrogen Uptake Efficiency Must Be Improved To Maintain a Himentioning
confidence: 99%
“…N fertilization was calculated using the balance sheet method that is commonly used in France for the main arable crops (Rémy and Hébert 1977;Parnaudeau et al 2009). The N doses were calculated as follows:…”
Section: Management Of N Fertilizationmentioning
confidence: 99%
“…O teor de clorofila total indica a eficiência na absorção da radiação solar pelas folhas e, como consequência, uma maior taxa fotossintéti-ca e maiores rendimentos de grãos (Mahama et al, 2016). A avaliação indireta de clorofila é uma importante ferramenta para determinações de práticas de manejo do milho e de outras culturas, visando à obtenção de altas produtividades aliadas à utilização racional de fertilizantes nitrogenados (Schulte et al, 2007).…”
unclassified